Muhammad Ali Sircar the first of the world's officially recognized student-author from British India - Rahman, Md. Lutfor 1949- (Dhaka, Bangladesh International Publications, 1991)
Biography of Muhammad Ali Sircar, b. 1923, retired civil servant from Bangladesh, who wrote Assam own copy book, a textbook in English for primary students, while he was a student of class X.
Keywords: Sircar, Muhammad Ali -- 1923